DESIGN OF USER INTERFACE/USER EXPERIENCE AUTOMATIC TELLER MACHINE RED WHITE USING DESIGN SPRINT METHOD AT BANK RAKYAT INDONESIA BRANCH OFFICE KEDIRI - Kurniawan, Mochammad; Amelia, Tan; Churniawan, Agus Dwi (Jurnal Sistem Informasi Universitas Dinamika, 2022)
ATM is one of the e-banking services used by banks. Currently, Bank Rakyat Indonesia Kediri Branch Office has 123 ATM machines spread across the city and district of Kediri that can be used by customers. Respondents who will be surveyed are bank customers and IT parties as well as ATM managers of Bank Rakyat Indonesia Kediri Branch Offices. The current ATM display is still a blue screen with white writing and writing. There are several problems experienced by users in operating ATMs from the absence of icons to make it easier for users, the form of display and writing that is less attractive to users, user satisfaction in operating the current ATM display, the suitability of the location of the buttons on the ATM, as well as the ease and understanding of users in operating the ATM.The design sprint method which consists of five stages in this research is expected to provide input for the design of the user interface and user experience in the form of a prototype. After validating using AB Testing, it has been found that prototype A is more chosen with a percentage of seventy-five percent (75%) than prototype B which is only twenty-five percent (25%) so it can be concluded that customers prefer using a more colorful ATM display and added icons so that the contents on the menu can be easily understood by users.